THE EFFECT OF PROFITABILITY ON FINANCIAL PEFORMANCE WITH GCG AND STOCK PRICE AS MODERATING VARIABLES - Rianto Rianto (ITB AAS Indonesia Surakarta, 2024)
Financial performance is one of the most vital aspects of a company to pay attention to because financial performance is the lifeblood of a company to continue production, attract investors and expand its market share. There are a number of factors that can influence the financial performance of a company, including profitability. Therefore, this research aims to analyze the effect of profitability on financial performance. Different from previous studies, this research uses the Good Corporate Governance variable and the Stock Price variable as moderating variables. This research is a quantitative research with an exploratory approach using secondary data obtained from the IDX and PT financial reports. Pulau Subur Tbk. The data used in the research were analyzed with smart PLS 3.0 software. The research results show that the Profitability variable has a positive and significant relationship with the Financial Performance variable. Apart from that, the GCG and Stock Pirce variables can moderate the influence of the Profitability variable on Financial Performance. Keywords: Profitability, GCG, Financial Pefromance, Stock Price. 1. INTRODUCTION The company's financial performance is one of the factors